The philosophy of science acconting - Torres Gallardo, Arturo (2012)
The accounting knowledge is rational in rendering coherent judgments and arguments, between their statements. However, according to the principles, and not to the formal development of the sciences, which can be rational or experimental, I argue that it is an experimental science. The accounting discipline is an applied science and it is in a maturation process, because of there is no dominant paradigm, but a multi-paradigmatic science. This proposal is based in found inside the accounting discipline the presence of three elements: the study object (the assets of the economic entity and its dynamics), the method (inductive-deductive), and predictive capacity, expressed in existing accounting models, which are evident. Therefore, under this modest perspective, the accounting discipline has an object of study, a method and predictive capacity, which gives it a status of science.